Les nuits contestataires des néo-charbonniers du Vercors : un chronotope forestier au service d’une hétérotopie - Christophe Baticle; Philippe Hanus (Revue de Géographie Alpine)
For around two decades the charcoal burning festivals of the Vercors have been bringing together a group of individuals – with libertarian and/or ecologist aspirations – for the space of a few weeks to produce an unusual chronotope with the support of the local inhabitants: the erection then carbonisation of a charcoal pit in the forest, around which will be added the village of the “neo-wood colliers” and the festive infrastructures according to the rhythm furnished by the progress of the combustion, in the fashion of a heterotopia contesting daytime life in the valley. Above and beyond the heritage aspect, this collective experience of the night in a mountain forest does not exclude variations in the realms of the imaginary, symbolic and political. Behind the pretext of charcoal, their protagonists unite through a spatial practice (the clearing) and refer to the two great guardian figures of the region: the wood collier ancestor and the resistance fighter as “clandestines of the night”. The chronotope thus set up therefore borrows from heterotopia and heterochrony insofar as the diurnal and especially nocturnal forest system constitutes “another space” in an atypical way of living the rhythms of daily life in connection (fantasised to a greater or lesser degree) with the History of the Vercors region. These festive metonyms of time and space are spatial and temporal anchor points which indicate how this experience is established in situ to challenge the dominant system.